PERBANDINGAN HASIL BELAJAR SISWA YANG MENGGUNAKAN MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) DAN TWO STAY-TWO STRAY (TS-TS) DI KELAS VII SMPN 17 KOTA BENGKULU - adisaputra, dandi; yensy B, nurul astuty; Herawaty, Dewi (Program Studi S1 Pendidikan Matematika FKIP Universitas Bengkulu, 2018)
The aim of the study was to find out whether the learning outcomes of students’ in match using learning model of Numbered Head Together (NHT) was more than the mean score of students learning outcomes using Two-Stay-Two Stray (TS-TS) in class VII of SMPN 17 of Bengkulu City. The study was quasi experimental research. The population in the study was the students of class VII of SMPN 17 of Bengkulu City, with class VII F as the experimental class applying Numbered Head Together (NHT) and class VII E as the control class applying Two-Stay-Two Stray (TS-TS). The technique of data collection conducted instrument of students learning outcomes test (posttest) which was essay. Based on the research results, it was obtained the learning outcomes of students’ using learning model of Numbered Head Together (NHT) was same with the learning outcomes of students using Two-Stay-Two Stray (TS-TS). It was proved by hypothesis test using t-test which was gotten tcount = 1,177 and ttable = 2,004 with a = 0,05. Since tcount < ttable , the it could be concluded the learning outcomes of students’ in match using learning model of Numbered Head Together (NHT) was same with the learning outcomes of students using Two-Stay-Two Stray (TS-TS) in class VII of SMPN 17 of Bengkulu City. Key Words : Experimental, Learning Outcomes, Assemblage, Numbered Head Together, Two Stay-Two Stray.